GAMBARAN PERSEPSI PASIEN INSTALASI RAWAT INAP MENGENAI BRAND EQUITY RUMAH SAKIT TINGKAT III BALADHIKA HUSADA JEMBER TAHUN 2018 - Dwi Novita Sari; Christyana Sandra; Sri Utami (Jurnal Ilmu Kesehatan Masyarakat, 2018)
Brand equity is a set of brand assets and liabilities linked to a brand name and symbol, which add to or subtract from the value provided by a product or service. For 3 years, Bed Occupancy Rate haven’t met the optimal standard and shows that the society is still less utilize inpatient services of Baladhika Husada Jember Third-Level Hospital. The objective of this study was describe inpatient's perception about brand equity of Baladhika Husada Jember Third-Level Hospital in 2018. This study used a descriptive study. Results showed that most of the respondents are female, in the age group >45 years old, living in Jember, last education are elementary school/equivalent, housewifes, family income ranged between Rp 1.1 million - Rp 2 million and methods of payment using BPJS Health insurance. Variable brand awareness is good enough because the majority of respondents choose Baladhika Husada Jember Third-Level Hospital as top of mind. Brand association through product attributes, intangible, customer benefits, relative price, and use/application are in good category. Perceived quality through performance, serviceability, reliability, features, conformance to specifications and results are in good category. Brand loyalty dominated by satisfied buyer.